ANALISIS MATERI PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM MTs KELAS VIII SEMESTER 1 BAB I DAN BAB II - Ahmad Anis; Muhammad Miftah; Nisya' Aulia Fadila; Ahsanu Nadiyya (STAI Pelabuhan Ratu, 2023)
History related to sequence of events and each event occurs at a certain time, likewise in Islamic history. Islamic history reveals the phenomena based on the facts of the historical development of Muslims from era to era. The purpose of this study was to analyze the contents of the teaching material of History of Islamic Culture students at the VIII grade Madrasah Tsanawiyah level published by the Indonesian Ministry of Religion in 2013 Curriculum. This study used library research, with descriptive analysis techniques through some literature. The results of this study indicate that the student book on the subject of History of Islamic Culture at the VIII grade has presented a material based on cognitive, affective, psychomotor domain, and students psychological development. Thus, it is expected that teachers can convey the material using variety methods, so that the students can easily understand and not bored, so learning goals can be achieved and improve the quality of education.